THE THEORY OF TAX PLANNING. - Hoffman, William H. (The Accounting Review, 1961)
This article focuses on the theory tax planning. Tax planning can be defined as the tax-payer's capacity to arrange his financial activities in such a manner as to suffer a minimum expenditure for taxes. When the designation tax planning is used, it really means effective tax planning. All tax planning does not reduce the tax liability to the desired minimum level. The tax planning that is not cut properly to suit the individual taxpayer may have the ultimately adverse effect of maximizing the tax. Tax planning involves the use of foresight and consequently it is concerned with future matters. Unfortunately, tax planning is often the product of a certain amount of hindsight. The taxpayer who learns, much to his distress, too late about the six-months holding requirement for securing the long-term capital-gains advantage is apt to profit by his mistakes in his future activities. Having been burned once, he is ready and willing to engage in the tax planning process. Tax evasion and tax avoidance should be distinguished. All too often these terms have become interchangeable with each other in the minds of the taxpayer. The failure to make any distinction between these separate concepts works to the discredit of the tax planning process and may lead to serious legal consequences.